New kissing bug (Hemiptera: Reduviidae: Triatominae) records from Napo and Morona-Santiago provinces with distribution updates in Ecuador - Soto Vivas, Ana (2018)
Four species of Triatominae (Hemiptera: Reduviidae) are reported in four localities in Ecuadorian Amazonia. Eratyrus mucronatus Stål, 1859, Rhodnius pictipes Stål, 1872 & Panstrongylus geniculatus (Latreille, 1811) in Napo Province, and Rhodnius robustus Larrousse, 1927 in Morona-Santiago Province. Two specimens of R. pictipes were found in an urban area of Tena City (capital province). These findings can indicate a risk of Chagas disease transmission in urban and peri-urban areas of the Amazonia.